THE USE DIGITAL STORY TELLING TO INCREASE STUDENTS INTEREST IN LEARNING IN THE NEW NORMAL ERA - Helina Nova Rina; Dian Arief Pradana; Devi Novitasari; St. Shabibatul Rohmah (RADJA PUBLIKA, 2023)
In this globalization era, technological developments are increasing rapidly. The use of media in learning is also increasingly diverse, ranging from traditional to modern. Especially in this Covid era, as educators we are required to be creative and innovative in choosing media in learning to increase students' interest in learning. The use of technological media in learning is one way that is used so that learning can continue during face-to-face meeting restrictions. Digital Story Telling is one of the appropriate learning media during this Pandemic era. Providing material in digital form is expected to be able to be conveyed to students without reducing student learning interest.